In the Readers’ Own Words: How User Content in the Catalog Can Enhance Readers’ Advisory Services - Spiteri, Louise F.; Pecoskie, Jen; Tarulli, Laurel (Reference and user services quarterly, 2016)
In the public library context, readers' advisory (RA) services, which aim to provide the right book in the hands of the user at the right time, is a central and longstanding core of the profession. In traditional RA services, knowledgeable library staff helps readers with their leisure-reading needs. In most public libraries, RA models are heavily based on the traditional reference-interview structure. The conversations start with a roving readers' advisor approaching a reader within the library, or a patron who approaches an RA staff member. This paper discusses two research studies conducted to examine the contribution of user-generated content in the form of tags and reviews in public library catalogs to both the description of fiction titles as well as its possible extension to RA services. Social services such as Amazon, LibraryThing, and Goodreads have long encouraged readers to share their reviews of books, and, particularly in the case of the latter two services, to contribute descriptive content to the titles in the form of tags.